COMPARATIVE ANALYSIS OF CARTOGRAPHIC MATERIALS, WHICH ARE USED IN SPATIAL PLANNING OF UKRAINE AND GERMANY - Палеха, Ю.; Айлікова, Г.; Остапенко, П. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
This article contains analyzed maps of state and regional levels. They were used in spatial planning of Ukraine and the Federal Republic of Germany. The possibility of improvement and simplification of the existing methodology for the implementation of territorial planning schemes based on the integration of environmental principles into the territorial planning of Ukraine based on the implementation of the landscape plan as an obligatory component in the implementation of regional planning schemes is analyzed. Key words: spatial planning, landscape plan, General scheme of planning the country's territory, law on spatial planning, spatial planning program.